Pengembangan Sistem Monitoring Cloud LMS berbasis Grafana, Prometheus dan Telegram di SMK Negeri 2 Yogyakarta - Muhammad Fauzan Rafi; Eko Marpanaji (Journal of Information Technology and Education (JITED), 2025)
SMK Negeri 2 Yogyakarta, as one of the schools actively improving its digital services to enhance the quality of education, faces challenges when the enhancement of digital services is not accompanied by the maintenance and monitoring procedures of its infrastructure. This study aims to develop a monitoring system enabling the ICT team to centrally monitor the cloud learning management system (LMS) and ensure the quality of the developed system using ISO/IEC 25010 software quality standards. The research methodology utilized the Waterfall Model, encompassing stages such as Communication, Planning, Modeling, Construction, and Deployment. The monitoring system was tested using ISO/IEC 25010 software quality standards for Functional Suitability, Usability, Reliability, and Portability aspects. The development resulted in a cloud LMS monitoring system based on Grafana as a dashboard, Prometheus as a data monitoring collector, and Telegram as a bot for mobile data monitoring and notifications. The developed monitoring system has met ISO/IEC 25010 quality standards: functional suitability with a good predicate of 1 (all functions operate well); usability with a good predicate of 71.6 (considered good if above 70); reliability with a success rate of 1 (success according to Telcordia standard 0.95); and portability with 100% support for all end-user applications.